Comparative Study of the Impact of Corruption on the Human Development Index - T. M. Zharlygassinov; A. Zh. Panzabekova; M. S. Dosmanbetova (Экономика: стратегия и практика, 2023)
The problem of corruption in state bodies remains one of the main ones regarding qualitative economic development. The reason for this is the significant negative impact of this phenomenon on the standard of living of citizens and the efficiency of the functioning of state bodies. However, the strength of such interaction may differ depending on the country and how conscientiously the employees of its state apparatus carry out their work. Thus, it is relevant to analyze the impact of corruption on the standard of living of citizens, which in the framework of this study is defined as an index of human development. Many scientific methods were used during the work: analysis, deduction, and abstraction. As part of the study, the negative impact of corruption on some important social spheres, such as healthcare, education, and others, as well as on the income level of citizens and the development of the shadow economy, was analyzed. The impact of corruption on the indicators of the human development index and its individual components was assessed. Subsequently, it was shown that there is indeed a certain interaction between these variables, which once again speaks of the role of the fight against corruption in the country. Also, having assessed the state of combating the unfair behavior of civil servants in Kazakhstan, recommendations were prepared to counter this phenomenon. This work brings new knowledge in terms of assessing the impact of corruption on the development of the country and its citizens.